Charity in the Laboratory: Matching, Competition, and Group Identity - Charness, Gary; Holder, Patrick (Management science, 2019)
We conduct a laboratory experiment in which participants can make donations to real charities. We vary whether the experimenter provides matching funds for any such donations, and whether there is individual or team competition for these matching funds. Our results indicate that providing matching funds for all donations does increase donations from 23% to 33% of the endowment. While individual competition for matching funds had nearly the same effectiveness as matching all donations, by far the most effective approach was to form (anonymous) teams that competed for matching funds; this led to donations of 47% of the endowment. We appeal to the notion of group identity to explain our results—participants seemed to be reluctant to “let down their team” in a competition. Our results can be seen as providing support for the notion that combining group identity and competition creates a motivation that can potentially be harnessed effectively for prosocial purposes. This paper was accepted by Uri Gneezy, behavioral economics.